The Effect of Obedience Pressure and Auditor Competence on Audit Judgment with Task Complexity as a Moderating Variable - Pebriyanti Palentina Sitorus; Bartolomeus Millenius Pele Lumban Batu (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence about the effect of Obedience Pressure and Auditor Competence on Audit Judgment with Task Complexity as a Moderating Variable. Design/Methodology/Approach – This research uses quantitative research. This research was conducted using a questionnaire distributed to both internal and external auditors who work at the Public Accounting Firm (KAP) and regional companies on the island of Java. A total of 30 questionnaires were distributed via e-mail and whatsapp, each questionnaire distributed contained 30 statements to be answered by respondents. From the distribution of questionnaires conducted, 30 respondents were obtained who had provided answers. To get the results of this study, researchers used PLS SEM version 3.0. Findings – The results of this study found that Obedience Pressure has a positive and statistically insignificant effect on Audit Judgment and Auditor Competence has a positive and statistically significant effect on Audit Judgment. The other findings are that Task Complexity does not strengthen the relationship between Obedience Pressure on Audit Judgment and Task Complexity does not strengthen the relationship between Auditor Competence on Audit Judgment. Research Limitations/Implications – This study focuses on Audit Judgment and the factors that influence it. This study adds Task Complexity as a moderating variable. Where the authors believe this research is a study that presents the latest evidence of Task Complexity as a moderating variable that focuses on internal and external auditors who work at Public Accounting Firms (KAP) and companies located in the Java island area. Researchers add the task complexity variable as a moderating variable because, they want to know whether the complexity of this task can strengthen the relationship between compliance pressure and auditor competence on audit judgment or even not affect the relationship between the two variables.